Desarrollo cognitivo e interacción asimétrica : notas para su estudio microgenético - Sylvia Sastre i Riba; Estanislau Pastor i Mallol (Universidad de La Rioja, 2013)
lnteraction is essential to study Cognitive Development. From a tripolar neoconstructivist point of view; we urge the necessity to discuss the meaning of "interaction" and the methodological bases studying it. Some questions arise: where is the infant in Cognitive Developmental Psychology today?, what is the infant's influence on interaction and viceversa? what is the effect of different kinds of interaction on cognitive development?, what interactional types and conditions could be established and what are their effects they have on individual cognitive development?. Empírical data from one research carried out are presented as a brief example of research into and reflections about these questions. Using microgenetic method, the results show us the possibilities and limitations of studyng and understanding the influence of interaction on cognitive development.